Analysis of Direct Gifts in Opening a Savings Account at Bank Syariah Indonesia in Program Spesial Rezeki Berkah Idul Adha - Rosadi, Imron; Sunaryo Mukhlas, Oyo (Yayasan Mentari Madani, 2025)
This study aims to analyze the suitability of the “Program Spesial Rezeki Berkah Idul Adha” program organized by Bank Syariah Indonesia (BSI) with the provisions of the fatwa of the National Sharia Council – Indonesian Ulema Council (DSN-MUI), especially related to the giving of prizes in fundraising. This program offers prizes in the form of sacrificial animals for customers who open a savings account with a certain placement of funds within a certain period of time. The method used in this study is a normative juridical approach with qualitative analysis, as well as a case study on the implementation of the BSI program. The results of the study show that there are a number of inconsistencies in the program with DSN-MUI fatwas, especially if the prize is promised definitively and is the main condition in the account opening contract, so that it has the potential to violate sharia principles such as the prohibition of riba, gharar, and maysir. However, this program can be declared in accordance with sharia if the prize is given without a prior promise, comes from bank funds, and is not part of the principal contract. This study recommends adjusting the reward mechanism so that promotional programs remain commercially attractive without violating applicable sharia principles